Robust object-oriented formulation of directed thermofluid stream networks. Issue 3 (3rd May 2020) - Zimmer, Dirk
ABSTRACT: Object-oriented formulation of thermal fluid streams often yields large non-linear equation systems whose numerical solution is difficult to achieve. This paper revisits the fundamental equations for thermal fluid streams and introduces a new term: the steady mass flow pressure p ˆ . Using this term, the equations can be brought into a form where all non-linear computations are explicit. This enables a robust and object-oriented formulation of even complex architectures. The modelling of aircraft environmental control systems is presented as one possible application example.